Communication Issues in Aotearoa New Zealand - (:unkn) unknown (https://www.unitec.ac.nz/epress/index.php/communication-issues-in-aotearoa-new-zealand-2/)
This edited volume introduces highlights of the academic interests and research activities of a number of staff at Unitec’s Department of Communication Studies, demonstrating the breadth and scope of the engagement of this academic collective with contemporary communication issues. Edited by Giles Dodson and Evangelia Papoutsaki, it is clear from the work that communication in Aotearoa New Zealand remains complex and continually under negotiation, as this country continues to be formed and reformed by processes of cultural encounter, by political and institutional change and by voices seeking to assert, to contest and to claim their presence – to represent and to be represented within contemporary New Zealand